Design and Build a Web-Based Village Information System for Acceleration of Village Services in Gampong Jantho Makmur - Ichsan; Feri Susilawati; Muhammad Haykal (LPPM Politeknik Aceh Selatan, 2023)
Today, information systems are very important in village governance. Jantho Makmur is one of the villages which currently still uses the conventional system in various ways, this method is not very effective considering that the times are developing and technology is getting more advanced. To provide efficient services to the public, we need an information system that can replace the conventional system. Based on this, a web-based village information system was developed. In its creation, this system uses the PHP programming language with Laravel as the Framework and MySQL as database management. This village information system provides an online feature for making certificates and public complaints. Submissions of letters and complaints that have been validated will be sent to the WhatsApp community in PDF format using the WhatsApp API Gateway. This application also implements Ajax and Datatables technology so it is very light and efficient to use. Besides that, this application also has features for filing incoming and outgoing letters, managing population data, writing articles and photo documentation of community activities.